Matthew ; v. 1 a commentary - Bruner, Frederick Dale (Dallas, TX Word, 1987)
Contents : v. 1 : The Christbook : Matthew 1-12. Includes bibliographical references
Keywords: Bible. N.T. Matthew I-XII -- commentaries; Jesus Christ -- person and offices -- biblical teaching